2017
DOI: 10.1016/j.redox.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in endothelial cells: Sensors and integrators of environmental cues

Abstract: The involvement of angiogenesis in disease and its potential as a therapeutic target have been firmly established over recent decades. Endothelial cells (ECs) are central elements in vessel homeostasis and regulate the passage of material and cells into and out of the bloodstream. EC proliferation and migration are modified by alterations to mitochondrial biogenesis and dynamics resulting from several signals and environmental cues, such as oxygen, hemodynamics, and nutrients. As intermediary signals, mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 123 publications
1
79
1
Order By: Relevance
“…Unlike tubular cells that are rich in mitochondria, the mitochondrial content in endothelial cells (ECs) is relatively modest (Caja & Enriquez, 2017). Nevertheless, these mitochondria might be important because renal ECs regulate vascular function, partly by modulating cell death, oxidative stress and nitric oxide (NO) bioavailability (Kluge, Fetterman, & Vita, 2013).…”
Section: New Findingsmentioning
confidence: 99%
“…Unlike tubular cells that are rich in mitochondria, the mitochondrial content in endothelial cells (ECs) is relatively modest (Caja & Enriquez, 2017). Nevertheless, these mitochondria might be important because renal ECs regulate vascular function, partly by modulating cell death, oxidative stress and nitric oxide (NO) bioavailability (Kluge, Fetterman, & Vita, 2013).…”
Section: New Findingsmentioning
confidence: 99%
“…In this study, we showed that short-term exposure (1 day Mitochondria exist in a dynamic equilibrium between fragmented and fused states, and mitochondrial dynamics is controlled by fission and fusion (Anderson et al, 2018;Shi et al, 2018). Increased mitochondrial fission and/or attenuated fusion lead to mitochondrial fragmentation and disrupt cellular physiological function (Caja et al, 2017). Previous studies indicate that the increased mitochondrial fission leads to mitochondrial ROS (mtROS) generation and elevated apoptosis in endothelial cells (ECs) of diabetic patients (Shenouda et al, 2011;Yang et al, 2018;Galloway et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…It has long been ascertained that mitochondrial content in ECs is modest (endothelial mitochondria occupy 2-6% of the cytoplasmic volume) compared with cardiac myocytes (32% of the cytoplasmic volume) and other cell types, as the energy requirements in ECs are relatively low and glycolysis is the major source of ATP production. In vitro and in vivo studies have shown that, apart from the well-known role of mitochondria in bioenergetics, they also play a prominent role in signalling cellular responses to environmental cues [10][11][12]. Two such important modes of signalling are their regulated production of mitochondrial reactive oxygen species (mROS) and their service as Ca 2þ sinks.…”
Section: Introductionmentioning
confidence: 99%